On Some Issues Promoting Successful Second Language Learning and Teaching - Zatikian, Anahit (Armenian Folia Anglistika, 2006)
The article attempts to address some of the issues related to successful second language teaching and suggest possible solutions. The success of teaching depends on the relevance of the favorable teaching atmosphere accompanied with the awareness of students’ objectives. It is necessary to use original texts and pay attention to the independent thinking and individuality of the students. The article pays special attention to the role of the teacher, his/her ability to present the material and other issues related to modern methods. These factors contribute to the promotion of the efficiency of second language teaching.